Optimalisasi Tanah Wakaf Terlantar di Indonesia: Analisis Komparatif Cash Waqf Linked Sukuk (CWLS) dan Sukuk Musyarakah - ST Naurah Nazhifah Resty; Nirdukita Ratnawati (Kartika: Jurnal Studi Keislaman, 2026)
Waqf is an Islamic social finance instrument with strong potential to support sustainable development. In Indonesia, much waqf land remains idle due to limited financing mechanisms and institutional capacity. The government has introduced Cash Waqf Linked Sukuk (CWLS) as an innovative financing solution, while Musharakah Sukuk, used in countries like Singapore, offers another alternative. This study analyzes and compares the suitability of both instruments for developing idle waqf land assets in Indonesia. This research employs a qualitative-comparative approach based on a review of reputable academic journals, regulatory documents, and data obtained from relevant institutions. The findings indicate that CWLS can serve as a financing instrument for idle waqf land assets, particularly when complemented by specific cooperation schemes with banking institutions. Meanwhile, Musharakah Sukuk is structurally more relevant for financing the development of idle waqf land assets due to its project-based and partnership-oriented nature; however, its implementation in Indonesia is constrained by the readiness of regulatory frameworks and supporting systems. This study makes a conceptual contribution and offers policy recommendations for the development of a sustainable waqf financing ecosystem in Indonesia.